Exploring Indonesia's Vernacular Architecture: Comparison of Environment and Culture Responsiveness - Aulia, Afina Nisa; Veronica, Selly (Talenta Publisher, 2024)
Culture, region, and climate are three fundamental aspects that influence vernacular architecture. As the largest archipelagic country in the world, Indonesia is rich in diversity of vernacular architecture, originating from different cultural backgrounds and natural characteristics. It is interesting to examine whether significant similarities or differences are reflected in two vernacular houses formed from other cultures, regions, and topographies, even though they have the same function: residence. In this research, architectural comparisons were made between Sundanese traditional houses with the natural character of the mountains in West Java and Banjar traditional houses in the coastal region of South Kalimantan. Data was obtained through the literature review and then analyzed using Bentley's theory of three aspects — functional-constructional, environmental, and socio-cultural; as well as seven criteria — permeability, variety, readability, robustness, visual suitability, richness, and personalization. The research results show that the differences between these two vernacular architectures are visible from the use of materials and the type of foundation used. Apart from that, an interesting fact was discovered that even though both of them have different cultures and regions, the shape of the roof, the position of openings such as windows and doors, and the location of the buildings in the same housing complex, these two vernacular architectures have similarities. It is analyzed that this is the response of both communities that is reflected in each of their vernacular architecture to the environment in the same climate, namely the tropical climate.